Combining the high‐dose/refuge strategy and self‐limiting transgenic insects in resistance management—A test in experimental mesocosms. (18th January 2018) - Zhou, Liqin; Alphey, Nina; Walker, Adam S.; Travers, Laura M.; Hasan, Fevziye; Morrison, Neil I.; Bonsall, Michael B.; Raymond, Ben
Abstract: The high‐dose/refuge strategy has been the primary approach for resistance management in transgenic crops engineered with Bacillus thuringiensis toxins. However, there are continuing pressures from growers to reduce the size of Bt toxin‐free refugia, which typically suffer higher damage from pests. One complementary approach is to release male transgenic insects with a female‐specific self‐limiting gene. This technology can reduce population sizes and slow the evolution of resistance by introgressing susceptible genes through males. Theory predicts that it could be used to facilitate smaller refugia or reverse the evolution of resistance. In this study, we used experimental evolution with caged insect populations to investigate the compatibility of the self‐limiting system and the high‐dose/refuge strategy in mitigating the evolution of resistance in diamondback moth, Plutella xylostella . The benefits of the self‐limiting system were clearer at smaller refuge size, particularly when refugia were inadequate to prevent the evolution of resistance. We found that transgenic males in caged mesocosms could suppress population size and delay resistance development with 10% refugia and 4%–15% initial resistance allele frequency. Fitness costs in hemizygous transgenic insects are particularly important for introgressing susceptible alleles into target populations. Fitness costs of the self‐limiting gene in this study ( P. xylostella OX4139 line L) were incompletely dominant, and reduced fecundity and male mating competitiveness. The experimental evolution approach used here illustrates some of the benefits and pitfalls of combining mass release of self‐limiting insects and the high‐dose/refuge strategy, but does indicate that they can be complementary.